PEMBERDAYAAN WARGA NEGARA DAN KEWIRAUSAHAAN SOSIAL: PEMUTUSAN MATA RANTAI ANAK JALANAN - Meidi Saputra (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2018)
This study aims at describing the citizen empowerment through social entrepreneurship as an effort to break the chain of street children. The design of this research is a case study, with the street children in Semarang as the subject of research. The research finding shows that citizen empowerment through social entrepreneurship plays an important role in breaking the chain of street children. The creation of Dynamic Learning methodis an important instrument in breaking the chain of street children. Dynamic Learning as a practice of social entrepreneurship has played an important role in giving the impact of citizen empowerment so as to improve the economy and social classes of marginalized citizens.